Scolopax rusticola Carrying Enterobacterales Harboring Antibiotic Resistance Genes - Valeria Gargano; Delia Gambino; Adriana Maria Oddo; Mariangela Pizzo; Arianna Sucato; Gaetano Cammilleri; Francesco La Russa; Maria Liliana Di Pasquale; Maria Giovanna Parisi; Giovanni Cassata; Giuseppe Giangrosso (MDPI AG, 2024)
The Eurasian woodcock (Scolopax rusticola) belongs to those bird species that make systematic migratory flights in spring and autumn in search of favorable breeding and wintering areas. These specimens arrive in the Mediterranean Area from northeastern European countries during the autumn season. The purpose of this study was to assess whether woodcocks can carry antibiotic resistance genes (ARGs) along their migratory routes. Although the role of migratory birds in the spread of some zoonotic diseases (of viral and bacterial etiology) has been elucidated, the role of these animals in the spread of antibiotic resistance has not yet been clarified. In this study, we analyzed the presence of beta-lactam antibiotic resistance genes. The study was conducted on 69 strains from 60 cloacal swabs belonging to an equal number of animals shot during the 2022-2023 hunting season in Sicily, Italy. An antibiogram was performed on all strains using the microdilution method (MIC) and beta-lactam resistance genes were investigated. The strains tested showed no phenotypic resistance to any of the 13 antibiotics tested; however, four isolates of Enterobacter cloacae and three of Klebsiella oxytoca were found to carry the blaIMP-70, blaVIM-35, blaNDM-5 and blaOXA-1 genes. Our results confirm the importance of monitoring antimicrobial resistance among migratory animals capable of long-distance bacteria spread.